Rancangan Receiver Lovalizer untuk Teknisi Menggunakan Register Transfer Level Software Defined Radio di Perum LPPNPI Cabang Utama Makassar Air Traffic Service Makassar - Suse Lamtiar; Muhammad Naufal Hilmi; Feti Fatonah (Politeknik Penerbangan Makassar, 2022)
Sultan Hasanuddin International Airport is one of the airports with the busiest traffic conditions in Indonesia. This makes ground check activities only possible when the traffic at Sultan Hasanuddin International Airport is quiet so that when there is a report from the pilot that the Localizer signal reception on the plane is unstable, the technician cannot immediately check the condition of the emitted signal with a ground check. Localizer at Sultan Hasanuddin International Airport does not use nearfield / far-field. This makes the technician unable to know the condition of the signal emitted from the Localizer other than when the technician is carrying out a ground check. For this reason, the authors made a Localizer receiver design for technicians using the Register Transfer Level Software Defined Radio (RTL SDR). This design uses RTL SDR as a device to receive Localizer signal emission. The signal received by the RTL SDR is then processed by the Python programming language to obtain 90 Hz and 150 Hz modulation signals, which are then displayed in the Web Application. This receiver design system is expected to be able to solve the problems that arise, where this text, as the person in charge of the operation and maintenance of flight navigation equipment, often does not know about the disturbance of the navigation equipment quickly.